Impact of anemia on the cardiovascular status in children with chronic kidney disease: A pilot study. (February 2022) - Bhagat, Naveen; Dawman, Lesa; Naganur, Sanjeev; Tiewsoh, Karalanglin; Kumar, Basant; Pratyusha, Kambagiri; Sharawat, Indar Kumar; Gupta, Krishan Lal
Summary: Background & aims: Myocardial dysfunction is one of the common complications in children with chronic kidney disease which results in significant morbidity and mortality. We aimed to find the impact of anemia with cardiac changes in children with chronic kidney disease (CKD). Methods: In this cross-sectional pilot study, 54 children (38 males) up to the age of 16 years with different stages of CKD, not on dialysis, were enrolled. Cardiovascular functions were evaluated using 2D-echocardiography using EPIC-7 (Philips) machine by an independent trained Pediatric Cardiologist. The M-mode measurements of the left ventricle were measured, indexed for body surface area and z-scores were calculated. They were divided into two groups i. e with and without anemia. Results: Out of the 54 children with CKD, children with and without anemia were 34 and 20 respectively. The end-diastolic volume was significantly higher in patients with anemia when compared with those without anemia (46.43 ± 16.49 ml vs 32.51 ± 4.98 ml). The mean left ventricular mass (59.54 ± 23.99 vs 37.24 ± 7.88 g) and end-diastolic thickness of the interventricular septum (0.73 ± 0.14 vs 0.54 ± 0.05 cm) was significantly elevated in CKD children with anemia. Conclusions: Left ventricular hypertrophy along with left ventricular dimension and left ventricular diastolic dysfunction was found to be significantly correlating with the degree of anemia. CKD children with anemia should be screened for underlying cardiac dysfunction and appropriate dietary modification and nutritional rehabilitation for iron deficiency should be addressed.